Persepsi Mahasiswa Program Studi Pendidikan Agama Islam dalam Penggunaan Chat GPT untuk Menunjang Proses Pembelajaran di Fakultas Tarbiyah IAIN Bone - Aqlisabarni, Dien; Yahya, Muhammad; Wahyuni, Sri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the perception of students from the Islamic Education Study Program towards the use of Chat GPT to support the learning process at the Tarbiyah Faculty of IAIN Bone. This research was conducted at Campus 1 of IAIN Bone using a descriptive qualitative research method. Data collection techniques included interviews, observation, and documentation. The data analysis techniques consisted of data reduction, data display, and conclusion drawing. The analysis results indicate that students from the Islamic Education Study Program (PAI) at the Tarbiyah Faculty of IAIN Bone have a tendency towards a positive perception regarding the use of Chat GPT in supporting classroom discussion processes. They assess that Chat GPT is effective in helping them formulate stimulating questions, simplify complex language, and enrich insights beyond the material presented in papers. Nevertheless, challenges such as potential dependency and the tendency to copy answers verbatim emerged. To overcome this, students strive to balance it with a critical attitude, ensuring material comprehension, and delivering the information in their own language. Meanwhile, students' perceptions of the quality of information obtained from Chat GPT within the context of PAI material varied; some felt the information was accurate and relevant to their learning, while others held a negative perception, believing the information was not always accurate, limited to what was asked, and not always up-to-date.